MOTOR VEHICLE STRUCTURE WITH CRASH BOX - ECKERT UWE; SCHEER RONALD (2015)
A motor vehicle structure is disclosed which includes a cross member, at least one side member connected to the cross member via a crash box. At least one strut supports a lateral region of the cross member, and the strut is connected to a molded part which is connected to the crash box and/or the side member.